MEMO Organisation Modelling Language (2): Focus on business processes - Ulrich Frank (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2011)
An enterprise model comprises various abstractions of an enterprise that represent both information systems and the surrounding action systems. These different models are integrated in order to avoid redundant work and to contribute to a tight and consistent integration of action systems and information systems. For this purpose, the method MEMO (Multi-Perspective Enterprise Modelling) features a family of modelling languages, each of which is aimed at representing specific perspectives and aspects of an enterprise. Within the MEMO languages, the Organisation Modelling Language (MEMO OrgML) is of outstanding relevance. Its specification is distributed on two reports. A previous report focussed on the specification of the organisation structure. This report presents the part of the language specification that allows for modelling business processes. It builds on a further previous report that presents the results of an extensive requirements analysis. The report starts with an analysis of basic concepts and a discussion of peculiarities related to the specification of a process modelling language. Subsequently, the language specification is presented. It comprises a meta model with supplementary constraints, detailed comments on core language concepts and a dictionary of the notational symbols in two variants. Finally, the use of the language is demonstrated with examples.
Keywords: 650